Radioisotope X-ray Fluorescence and Neutron Activation Analyses of the Trace Element Concentrations of the Rainbow Trout - Başsarı, A; Şener, E; Yıldız, M; Kuçer, R; Kaplan, Z; Doğan, G; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (CZECHOSLOVAK JNL OF PHYSICS, FYZIKALNI USTAV AV NA SLOVANCE 2, PRAGUE 180 40, CZECH REPUBLIC, 1999)
The muscles and livers of the ten rainbow trouts ( Oncorhynchus mykiss; N, 1752) obtained from Sapanca, Aquaculture Facility of Aquatic Products Faculty, The University of Istanbul (Turkey), have been analysed quantitatively for some minor elements using the radioisotope energy dispersive X-ray fluorescence (EDXRF) and neutron activation analysis (NAA) methods. It was found that samples contain Na, K, Ca, Sc, Cs, Fe, Co, Cu, Zn, Se, Br, Rb, Sr, Au, La and Ce in different amounts. Comparison of the results with those of reference river fish samples indicated that agricultural rainbow trout samples from Sapanca region have higher Fe level.
Keywords: scattered radiation; samples; saçılan radyasyon; örnekler